Protection of Human Rights—The Role of the ECHR - Paczolay, Péter (International Law From A Central European Perspective, 2022)
In present-day Europe a multilevel protection of human rights has developed. Freedoms in Europe are protected at the national level, the Council of Europe level, and the European Union level. National courts, especially constitutional courts, defend rights based primarily on the ground of the national constitutions, but also by the international legal instruments. The Court of Justice of the European Union protects the rights embodied in the Charter. The European Court of Human Rights protects the freedoms and rights enshrined in the European Convention of Human Rights. The chapter analyses only the developments of jurisprudence of the Strasbourg Court, and focuses on three distinct subjects: the protection of ethnic minorities, the right to education, and the human rights challenges of the digital era. The Court considers the Convention a “living instrument,” and by the way of its “innovative interpretation” can protect human rights even outside the area that the Convention’s text strictly covers. Through this flexible approach, the Court is able accommodate human rights protection to changing political and social environments. Nevertheless, as the first subject indicates, the efforts are not always successful. In the area of the protection of ethnic and national minorities the result cannot be called a success story, and the case-law is unfortunately contingent. Contrariwise, the subject of education rights provides an example of how the Court could enlarge the applicability of a right previously interpreted very narrowly and elevate the standard of assessment higher than its previous case-law. The Court could also give adequate answers to the challenges of the digital era, extending human rights jurisprudence to the online world. The approach of the Court is illustrated in connection with two fundamental rights protected by the Convention: first, the Internet and freedom of expression; second, data-protection and retention issues relevant for the Internet in the context of the right to privacy. KEYWORDS: European Court of Human Rights, minority rights, right to education, internet